2008
DOI: 10.1039/b716024k
|View full text |Cite
|
Sign up to set email alerts
|

OH radical reactions with phenylalanine in free and peptide forms

Abstract: Density functional theory has been used to model the reaction of OH with l-phenylalanine, as a free molecule and in the Gly-Phe-Gly peptide. The influence of the environment has been investigated using water and benzene as models for polar and non-polar surroundings, in addition to gas phase calculations. Different paths of reaction have been considered, involving H abstractions and addition reactions, with global contributions to the overall reaction around 10% and 90% respectively when Phe is in its free for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 57 publications
14
27
0
Order By: Relevance
“…The solvent cage effects have been included according to the corrections proposed by Okuno,35 taking into account the free volume theory 36. These corrections are in good agreement with those independently obtained by Ardura et al37 and have been successfully used by other authors 38–44…”
Section: Computational Detailssupporting
confidence: 91%
“…The solvent cage effects have been included according to the corrections proposed by Okuno,35 taking into account the free volume theory 36. These corrections are in good agreement with those independently obtained by Ardura et al37 and have been successfully used by other authors 38–44…”
Section: Computational Detailssupporting
confidence: 91%
“…However, the degree of these preferences varied due likely to differences in experimental design. The o-:p-:m -tyrosine isomer ratio in aqueous solutions following irradiation has been found to vary between 1.0:0.60:1.0 ( o-:p-:m -tyrosine) (Simic et al, 1985) and 1.0:0.60:0.28 (Solar, 1985)—the later data is consistent with mathematical modeling predicting a ratio of 1.0:0.37:0.11 (Galano and Cruz-Torres, 2008). The ratio of the tyrosine isomers formed also varies depending on the chemical oxidizer utilized or the addition or absence of secondary oxidants following solution irradiation.…”
Section: Formation Of Abnormal Tyrosine Isomers Meta- and Ortho-tsupporting
confidence: 70%
“…24 Different behavior of mand o-Tyr is an interesting finding of our study, supported by the data of others as well, an explanation of which is unknown as yet. 9 Regarding p-Tyr, serum levels of the physiological amino acid were lower at the beginning of the study compared to those of controls. During the study period, serum p-Tyr showed an increasing tendency, which finally led to the normalization of p-Tyr levels.…”
Section: Discussionmentioning
confidence: 90%